2019
DOI: 10.1016/j.joule.2019.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Conversion of Cellulose to High-Density Aviation Fuel

Abstract: High-density polycycloalkanes were first produced with cellulose by a highly integrated route that features a selective hydrogenolysis of cellulose to 2,5hexanedione under mild conditions, followed by the direct synthesis of polycycloalkanes with 2,5-hexanedione and hydrogen over a dual-bed catalyst system. The polycycloalkane mixture as obtained has a high density (0.88 g mL À1 ) and low freezing point (225 K). In real application, they can be used as advanced aviation fuel or additives to improve the volumet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
92
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(95 citation statements)
references
References 25 publications
2
92
1
Order By: Relevance
“…The pathway described above resulted in a 38 % overall yield for the conversion of 1 to 4/5 . However, other researchers have reported that nearly quantitative yields of 2 can be obtained through the use of a biphasic reaction system [47] or a solid base catalyst [48] . In addition, although we achieved a 75 % isolated yield of 3 after the chemoselective hydrogenation step, we obtained a 98 % conversion of 2 to 3 .…”
Section: Resultscontrasting
confidence: 54%
See 3 more Smart Citations
“…The pathway described above resulted in a 38 % overall yield for the conversion of 1 to 4/5 . However, other researchers have reported that nearly quantitative yields of 2 can be obtained through the use of a biphasic reaction system [47] or a solid base catalyst [48] . In addition, although we achieved a 75 % isolated yield of 3 after the chemoselective hydrogenation step, we obtained a 98 % conversion of 2 to 3 .…”
Section: Resultscontrasting
confidence: 54%
“…Therefore, it may be feasible to improve the yield of 4/5 to greater than 80 %. Recent work by Zhang et al [48] . has demonstrated a 71.2 % yield of 1 from cellulose.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“… 5 9 Among these downstream compounds, 2,5-diformylfuran and 2,5-furandicarboxylic acid could be used as monomers for renewable polyesters, while 2,5-hexanedione, 2,5-dimethylfuran, cyclopentanone, and furfuryl alcohol all could be used to produce liquid fuels. 10 14 Due to the versatility of these biomass-derived furanic compounds, great efforts are devoted to efficiently produce HMF and furfural from renewable biomass during the past decades.…”
Section: Introductionmentioning
confidence: 99%